Study the Effect of Thickness on Optical Properties of Polymer PMMA Thin Films Preparated by Spin Coating Method (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In this research, study the effect of thickness on the optical properties for polymer poly(methyl methacrylate),that the  films were prepared  by spin coating method. Some of optical properties of poly(methyl methacrylate)film  have studied, which includes (energy gap , absorbance spectrum, transmittance  spectrum, reflectance ,extinction coefficient, refractive index, absorption coefficient, imaginary and real dielectric constant) ,this study shows that having different properties due to the difference in thickness .The measurements were taken for different thickness (206,116,87,66,47 nm  ) and different number of rotation (1000,2000,3000,4000,5000 rpm) respectively.